2001
DOI: 10.1038/sj.ijo.0801573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term energy restriction and physical training on haemostatic risk factors for coronary heart disease in obese children and adolescents

Abstract: OBJECTIVE:To study the changes of haemostatic risk factors for coronary heart disease during a weight reduction programme in obese children and adolescents. DESIGN: A short-term longitudinal study. SUBJECTS: Thirty-seven obese white girls (age, 12 AE 1.8 y; body mass index (BMI), 26.9 AE 5.25) and 19 obese white boys (age, 11.9 AE 1.7 y; BMI, 26.2 AE 5.2). MEASUREMENTS: Fibrinogen, factor VII coagulant activity, von Willebrand factor antigen, and soluble P-selectin were determined before and after a 3 week pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…However, it is well demonstrated in adults that regular physical activity and exercise training typically results in lower TNF-α levels [6]. Several studies have demonstrated IL-6 to show a consistent reduction following exercise training [24,25] or to be lower in children/youth who are more physically active [40,42]. In these studies the magnitude of the effect of physical activity/exercise was such that IL-6 values were 26-49% lower.…”
Section: Association Between Physical Activity/exercise Training and mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is well demonstrated in adults that regular physical activity and exercise training typically results in lower TNF-α levels [6]. Several studies have demonstrated IL-6 to show a consistent reduction following exercise training [24,25] or to be lower in children/youth who are more physically active [40,42]. In these studies the magnitude of the effect of physical activity/exercise was such that IL-6 values were 26-49% lower.…”
Section: Association Between Physical Activity/exercise Training and mentioning
confidence: 99%
“…A few studies have shown either differences in IL-6 with increasing degree of obesity [23], or an association between IL-6 and surrogates of adiposity such as waist circumference [22]. However, weight reduction programs in youth have demonstrated that decreases in body mass also resulted in lower IL-6 concentrations in overweight children [24]. Because IL-6 is so highly variable, relatively large sample sizes are required to demonstrate differences related to obesity in this cytokine [23].…”
Section: Obesity Surrogates (Increased Adiposity)mentioning
confidence: 99%
“…Obesity in adulthood is also associated with elevated haemostatic variables [15,16]. Even in childhood, adiposity is associated with unfavourable concentrations of haemostatic factors [17][18][19][20]. Inactivity or low levels of physical activity have been associated with increased haemostatic factors [18,21,22].…”
Section: Introductionmentioning
confidence: 96%
“…Cardio-metabolic risks may be influenced by both genetic factors and lifestyle choices (Gallistl, Sudi, Cvirn, & Borkenstein, 2001). Whilst genetic factors cannot be modified, lifestyle risk factors such as smoking, exercise, and dietary intake can be modified.…”
Section: Introductionmentioning
confidence: 99%